If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-11)(-15) = y Multiply -11 * -15 165 = y Solving 165 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 165 + -1y = y + -1y Combine like terms: y + -1y = 0 165 + -1y = 0 Add '-165' to each side of the equation. 165 + -165 + -1y = 0 + -165 Combine like terms: 165 + -165 = 0 0 + -1y = 0 + -165 -1y = 0 + -165 Combine like terms: 0 + -165 = -165 -1y = -165 Divide each side by '-1'. y = 165 Simplifying y = 165
| 7p-5(3+p)= | | 6.42-10d=25 | | 6x^2+45x=180 | | 2(3t-8)-4t=2 | | -x-12=45 | | 1-8m=-5m+16 | | 8a-4-4a=6-a | | 3x-11=30 | | x/2+2/3=3/4 | | v=x(25-2x)(12-2x) | | 7p-5(3+p)=7p-15-5p | | -16=4a+2a | | 16.7d+66.7=25d+-.5 | | .666(5)= | | 3.5s-7.3=-7.3+2.6s | | (2x-11)/3=4+x | | x+7/2=7 | | -8x-16=-8(2x-6) | | -16=14a+2a | | 16n+1=80 | | 5-(3-f)-5=6(3-f) | | (5x/2)=3x+5 | | (2x-11)/3=4/3+x | | 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 |